2016
DOI: 10.21037/jovs.2016.07.16
|View full text |Cite
|
Sign up to set email alerts
|

Robotic esophagectomy

Abstract: esophagectomy should be considered. If EMR is performed in the context of Barrett's esophagus, radiofrequency ablation (RFA) to promote regression of the Barrett's should also be considered. Patients with persistent high-grade dysplasia after attempted RFA should also be considered for esophagectomy. EquipmentThe Da Vinci Surgical System is currently the only FDAapproved robotic system for lung surgery. The surgeon sits at a console some distance from the patient who is positioned on an operating table in clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The robotic approach to esophagectomy has been described by several authors (24,25), and was the object of a recent large review by Harbison et al comparing outcomes of robotic assisted versus non-robotic minimally invasive esophagectomy for esophageal cancer using the NSQIP database. They found robotic esophagectomy to be feasible on a larger scale with outcome similar to the standard of care regarding adequacy of the oncologic resection and complications (26).…”
Section: Role Of Robotic Surgerymentioning
confidence: 99%
“…The robotic approach to esophagectomy has been described by several authors (24,25), and was the object of a recent large review by Harbison et al comparing outcomes of robotic assisted versus non-robotic minimally invasive esophagectomy for esophageal cancer using the NSQIP database. They found robotic esophagectomy to be feasible on a larger scale with outcome similar to the standard of care regarding adequacy of the oncologic resection and complications (26).…”
Section: Role Of Robotic Surgerymentioning
confidence: 99%
“…Therefore, he changed the technique from hand sewn to stapled anastomosis. Moreover, patient selection was modified in terms of nutritional status, cardiopulmonary performance and risk factors related with liver disease [86,87].…”
Section: Kumar Et Al Published a Review On 295 Proceduresmentioning
confidence: 99%
“…At multivariate analysis, preoperative concurrent chemoradiation was a risk factor for pulmonary complications. In extensive mediastinal lymphadenectomy, Broussard et al (38) Causes for these high rates were identified in anastomotic complications and wrong selection of patients. Therefore, corrective actions were taken.…”
Section: Ramiementioning
confidence: 99%